ACTION RESEARCH : IMPROVING STUDENTSâ SPOKEN INTERACTIONS THROUGH POSTER SESSION - Seftika, Seftika (JURNAL SMART, 2015)
AbstractÂ Spoken interaction is beneficial in learning a language. In fact the classrooom interaction did not take place well. Due to the lack of studentsâ interaction, this study aimed to improve studentsâ spoken interaction through Poster Session. A classroom action research was carried out at the English major students at the fourth semester of STKIP Muhammadiyah Pringsewu Lampung.In collecting the data the researcher used observation, test, and documentation. The data collected were analyzed and synthesized both qualitatively and quantitatively, and then meaning and interpretation were built to know clearly the process which was occurred during the research. The results indicate that there is improvement of Studentsâ spoken interaction using Poster Session. Poster Session facilitates students to practise English spoken interaction, it enhances them to be involved in learner-learner interaction. Due to the fact that their interaction is great, it influences their speaking skill. Â Key Words: Interaction, speaking, Poster Session